Analysis of attitudinal assessment in the education of mid-level nursing professionals - Maria Aparecida Soares Viana; Cinira Magali Fortuna; Flávio Adriano Borges; José Renato Gatto Júnior; Silvia Matumoto; Maria José Clapis (Universidade Federal de Goias, 2016)
This is a qualitative study with the objective to analyze how the teaching and assessment of attitudinal contents in the education of mid-level nursing professionals have been carried out. Data were collected through documentary analysis and two focus group sessions with the participating teachers. The sessions were recorded, transcribed and analyzed by means of thematic content analysis. Two main themes were identified: assessment in the teaching-learning process of nursing technicians and teaching and assessment of attitudinal contents in the education of nursing technicians. In conclusion, attitudinal assessment is performed unsystematically, despite being considered a procedural method. Although the institution under study relies on a faculty with knowledge of other teaching and assessment approaches, there is no overcoming the disciplinary logic, theory-practice separation and summative assessment.